Pengaruh Teknik Negoisasi pada Platfrom Live Shope dalam Peningkatan Penjualan - Syamanda, Nurani; Silalahi, Esra; Limbanadi, Imelia; Dhia, Friska; Muhammad, Ari (Universitas Methodist Indonesia, 2024)
In today's digital era, electronic trading platforms such as live shopping have become increasingly popular as a primary sales channel for many businesses. Live shopping combines elements of interactivity and immediacy, allowing sellers to communicate in real-time with potential buyers. This study aims to investigate the impact of negotiation techniques used during live shopping sessions on the Shopee platform on increasing sales. Using a quantitative approach, this research collected data from 100 sellers who actively used live shopping on Shopee for six months. The negotiation techniques analyzed include tactics such as limited-time offers, progressive discounts, and responsive direct interactions. The results of the statistical analysis indicate that the effective use of negotiation techniques significantly increases sales volumes. This research provides new insights for online sellers on how to optimize their sales strategies and suggests that training in negotiation techniques should be an integral part of the seller's preparation to maximize their sales potential on live shopping platforms.